DA’I FASHION AND NON-VERBAL COMMUNICATION: Public Perspectives in Southern Tapanuli - Rafiq, Mohd.; Dianto, Icol (UIN Sumatera Utara, 2025)
Abstract: This study examines how religious values, social norms, and cultural expectations influence public perceptions of preacher attire in regions deeply rooted in local traditions. A qualitative approach was employed, utilizing in-depth interviews and participatory observation for data collection. The research sample consisted of purposefully selected local community members from diverse age groups and social backgrounds. The findings indicate that preacher fashion in South Tapanuli is perceived as a reflection of religious devotion and personal integrity. Traditional clothing styles, along with accessories such as the peci and sarong, symbolize commitment to Islamic principles and respect for local customs. However, some view certain aspects of preacher attire as a marker of exclusivity or social status. Overall, the community perceives preacher fashion as a bridge between religious identity and local culture, serving as both a medium for da’wah and a representation of social values.Keywords: Islamic propagation, Da’i, Perception, Fashion, Southern Tapanuli, Non-verbal Communication